Union Territory of Pondicherry Fourth Five Year Plan - Planning Commission (Planning Commission)
The Union Territory of Pondicherry comprises four settlements, covering an area of about 481.8 sq. K.Ms. with a population of 3.69 lakhs according to the 1961 Census. The Pondicherry region(290.1 sq. K.Ms) is on the east coast, about 160 K.Ms. south of Madras. Pondicherry is not a contiguous area but is interspersed with enclaves of Madras State. It consists of 267 villages, with a total population of 2.59 lakhs. About 160 K.Ms. further south on the east coast, lies the Karikal region (158.0 sq. K.Ms.) consisting of 118 villages, with a population of 84,000. Up- north near Kakinada in Andhra Pradesh, 800 K.Ms. from Madras, is the small enclave of Yanam, with four villages covering an area of about 20.7sq. K.Ms. with a population of 7,000. In the west coast, 160 K.Ms. south of Mangalore lies the Mahe region (10.4 sq. K.Ms.) consisting of 3 villages with a population of 19,500. The pressure of population in these settlement is much higher than in the adjoining States. The rate of growth of population is more or less same as in the adjacent States.
Draft Preliminary Memorandum